Nurses' Perception about Patients' Safety Culture in Mosul City - Tameem Thamir Mayouf (College of Nursing,University of Mosul, 2017)
Background and Aim: Perception of patients' safety cultures is fundamental in the process of improving patient care. The presence of many disciplines in healthcare organizations has necessitated the inclusion of the viewpoints of all workers from managers to technicians. The study aimed to assess the nurses' perception about patient's safety culture. Materials and method: cross sectional (descriptive) design was selected for this study, 125 nurses was participated in the study who work in different health departments: wards, emergency unit, intensive care units, operating room. The study was carried out from (1st November 2013 to 10th April 2014), Likert-type response scales was adopted to measure the nurses' perception about patient safety, which consist of two parts, part one covered the demographic data for nurses (Age, Gender, educational level, years of experiences, work time and workplace). Part two; assessed the nurses' perception, consists of four sections covered work area, supervisor relationship, communications and frequency of events reported. Results: The findings indicated that nurses were more positive about overall perceptions of safety, teamwork within units and supervisor expectations and actions promoting, while 69.6% of event reporting, and 55.6% for communication dimensions was negatively response among nurses' perception. Nurses' age, educational level and workplace, were not significantly associated with their perception regarding overall perceptions of patient safety dimension, only nurses' age was significantly associated with their perception regarding frequency of event reporting. Conclusion: The majority of nurses hadpositive responses toward teamwork within units. While most of the sample has negative responses toward frequency of events reporting, about half of nurses has positive responses to patient safety culture toward; overall perception of safety, communications openness, non-punitive responses to errors and staffing dimensions. Recommendation: the study recommended to encourage the reporting action, which can prevent certain errors from happening and improve patient's safety concept in nurses. Keyword: Perception, Culture, Patients' safety culture, nurses.